(untitled) - Woodson, R. Dodge (New York, 2003)
The concept of this book is to provide readers with a definitive guide to water well and septic systems. There is no other book available on this subject that is as current or exhaustive including key elements required to install, inspect, maintain, repair, and replace private water and sewage supplies. Laced throughout is code commentary based on the most current International Code pertaining to septic systems (International Private Sewage Disposal Code). Current standards from the American Water Works will be offered including Water Wells - A100-97 and Disinfection of Wells - C 654-97. There has never been a mainstream book that includes this code and standards information. "Water Wells and Septic Systems Handbook" is destined to be the most valuable book available on the subject.
Keywords: Septic tanks